AT-THARIQAH AL-ITTISHALIYAH (COMMUNICATIVE METHOD) WA TATHBIQUHA FI TA'LIM AL-LUGHAH AL-'ARABIYAH: الطريقة الاتصالية (Communicative Method) وتطبيقها في تعليم اللغة العربية - Shofwatul Fu'adah; Nazilatil Maghviroh (Lahjah Arabiyah: Jurnal Bahasa Arab dan Pendidikan Bahasa Arab, 2023)
The Ittishaliyah or communicative method in learning language including Arabic is to make the students ability to communicate or interact with Arabic become a top priority compared to mastery of grammar. Because the main goal in the communicative approach is that students are able to communicate with Arabic in various social and functional situations. Some sources argue that communicative is an approach, there are also those who argue that it is a method. Therefore this research uses the literature study method where the data comes from various sources of literature that are relevant to this research. This study aims to explore the Ittishaliyah method. The points in this study include the history of the emergence of the Ittishaliyah method, the theories that used by this method, characteristics, and the practice in learning Arabic language. From analyzing the data, the researcher reveals some conclusion that the Ittishaliyah method came to achieve what the Sam’iyah Syafahiyah method failed to achieve in the field of language education. Ittishaliyah method is the method of teaching a second or foreign language that achieves communicative competence as the purpose of education and prioritizes students' creativity in speaking practice.